Religion on an Ordinary News Day in Australia: Hidden Christianity and the Pervasiveness of Lived Religion, Spirituality and the Secular Sacred - Weng, Enqi (Journal of religion, media and digital culture, 2021)
Abstract While Australia is most frequently referred to as a secular country, this Melbourne media study found that diverse expressions of religion, spirituality and the secular sacred were located across Australian political, public and sociocultural life in overt and subtle ways. Christianity remains dominantly represented across different news genres, while Aboriginal Spirituality had little mention despite its deep pre-colonial history. Islam received the most, and largely negative, attention across geopolitical and national issues. Findings from the Australian Royal Commission into Institutional Responses to Child Sexual Abuse were also prominently featured focused on Christianity and Judaism. Eastern religions and practices, such as Buddhism, Hinduism and yoga, received comparatively less coverage, but were depicted mostly positively, as was spirituality. Findings from Australia demonstrate that religion, spirituality and the secular sacred are embedded in pervasive ways that more accurately reflect lived religious and spiritual realities than census data and previous studies have documented.